Model City Branding Melalui Revitalisasi Sungai Cikapundung - Iis Saidah; Agustin Rozalena (MediaTor (Jurnal Komunikasi), 2019)
This study aims to construct the city branding model through the revitalization of the Cikapundung River. It is a qualitative case study research formulated by contruction paradigm.  Data collection techniques were carried out through Focus Group Discussions (FGD), nonparticipant observation, in-depth interviews and literature as well as data analysis techniques with the Interactive Model. The results are 1). The process of Bandung city branding established through Cikapundung revitalization river effects, which boosted the specific artificial tourism in  Bandung city 2). The branding stategy to promote the river are achieved by publicizing the artificial tourism superiority of Cikapundung river as a tourism spot through some  events, creating the same perception about the river’s image among people and increasing the attractiveness of  Cikapundung river. 3). The city branding design has an Octagone design aspects and adding other important aspect that is preservation of the environment that formed Nanogone model. The conclusion are 1). The revitalization of cikapundung river  create branding of Bandung city 2). The branding stategy increase tourist visit to Bandung city 3). Preservation the environments as forming  the Nanogone design raise the awareness about environments.